2022
DOI: 10.1097/opx.0000000000001891
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Tear Film Parameters in Smokers and Subjects with a High Body Mass Index

Abstract: SIGNIFICANCE:The current study compares the ocular tear film parameters in three different groups using a single noninvasive, practical, and easy-to-use tool.PURPOSE: This study aimed to assess the tear film in smokers, those with a high body mass index (BMI), and healthy subjects using the EASYTEAR view+.METHODS: Thirty men with a high BMI (>25 kg/m 2 ; 24.4 ± 6.4 years), 30 smokers (25.1 ± 6.1 years), and 30 healthy subjects (22.2 ± 3.5 years) were recruited. Each subject completed the Ocular Surface Disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…As such, the association between dry eye and smoking has been clearly established. The median OSDI score in the current study was comparable to those reported for smokers and subjects with a high body mass index [ 18 , 47 ], but lower compared with the OSDI scores for subjects with diabetes and refractive errors [ 48 50 ].…”
Section: Discussionsupporting
confidence: 73%
“…As such, the association between dry eye and smoking has been clearly established. The median OSDI score in the current study was comparable to those reported for smokers and subjects with a high body mass index [ 18 , 47 ], but lower compared with the OSDI scores for subjects with diabetes and refractive errors [ 48 50 ].…”
Section: Discussionsupporting
confidence: 73%
“…It should be noted that the median OSDI score for the control group (median 6. [39][40][41] For the study group, the median OSDI score (median 8.0 (IQR 6.8)) was comparable to smokers (median 8.3 (IQR 16.2)) 39 and lower than for subjects with high BMI (median 10.2 (IQR 16.4)), 39 diabetes (median 12.0 (IQR 8.3)), 40 myopia (median 11.0 (IQR 7.5)), 41 and hyperopia (median 10.0 (IQR 33.5)). 41 As reported in a study by Alanazi et al, in subjects with high BMI, there were strong correlations between age and OSDI scores (r = 0.522; p = 0.018), tear meniscus height (TMH) measurements (r =-0.503; p = 0.024) and tear ferning (TF) grades (r = 0.579; p = 0.007).…”
Section: Discussionmentioning
confidence: 99%
“…This device also measures NITBUT, TMH, and LLP. A cutoff of NITBUT than 10s was employed to indicate dryness, while a TMH value below 0.2 mm was considered indicative of dryness [20] . Lipid Layer Pattern Lipid layer patterns were evaluated for each participant based on images captured using EASYTEAR View+ (EASYTEAR S.R.L., Via Maioliche, Trento, Italy).…”
Section: Non-invasive Tear Break-up Time and Tear Meniscus Heightmentioning
confidence: 99%